1966
DOI: 10.1002/j.2164-4918.1966.tb03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Guidance: After the Fall

Abstract: Despite the recent condemnations of vocational guidance, the importance of Parson's contributions for current theory and practice remains unaltered. A number of commonly held assumptions regarding the use of tests as self‐appraisal devices, classification of the work environment, primary versus vicarious experiences, sequential study of self and work, dissemination of occupational information, and modern theories of vocational development, are considered and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1968
1968
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The large differences on the observed means obtained on the Vocational Development Inventory indicates divergences in vocational maturity among the five groups included in this present study but particularly between the inner-city groups and the suburban group. This supports the contentions (Calia, 1966;Hall, 1963) that vocational maturity and possibly other developmental constructs are linked to certain cultural and socioeconomic determinants. The inner-city groups, with the possible exception of the white segregated group, seem not to be aware of the factors considered important for vocational planning at the eighth-grade level.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The large differences on the observed means obtained on the Vocational Development Inventory indicates divergences in vocational maturity among the five groups included in this present study but particularly between the inner-city groups and the suburban group. This supports the contentions (Calia, 1966;Hall, 1963) that vocational maturity and possibly other developmental constructs are linked to certain cultural and socioeconomic determinants. The inner-city groups, with the possible exception of the white segregated group, seem not to be aware of the factors considered important for vocational planning at the eighth-grade level.…”
Section: Discussionsupporting
confidence: 85%
“…The developmental theorists, however, have linked the process of vocational choice to particular cultural determinants and have premised their theories on middle-class phenomena (Calia, 1966). Noticeably absent from the literature is research related to the vocational development of individuals who are not members of the middleclass Caucasian society.…”
mentioning
confidence: 99%
“…While this observation is not new to the field (Calia, 1966;LoCascio, 1967LoCascio, , 1974Smith, 1976;Tyler, 1967), in recent years scholars have argued that vocational psychology is still dominated by a worldview that implicitly values autonomy and individualism (Cook, Heppner, & O'Brien, 2002;Peterson & González, 2005;Richardson, 1993;Schultheiss, 2003). Specifically, scholars have critiqued the prevailing mode of theory as reflecting a linear career 2000).…”
mentioning
confidence: 91%
“…Hall (1963) has suggested that psychologists have looked at homogeneous populations and Gribbons and Lohnes (1968) note that too little vocational development research has been directed toward the less academically able students and students from lower socioeconomic groups. Some writers have been concerned that theory and research relative to vocational maturity have been based on middle-class groups (Amos & Grambs, 1968;Calia, 1966;Tyler, 1967) and call for research relevant to the lowerclass individual.…”
mentioning
confidence: 99%